Pluralisme Agama dan Implementasinya dalam Pendidikan Islam (Perspektif Al-Qur’an) - Kisman kisman (PALAPA, 2017)
The reality of a nation that shows the existence of conditions of cultural diversity, defines the choice to adopt pluralist principles. In the principle of pluaralism there is an awareness that the nation is not single, but composed of many different components. Indonesia is one of the largest pluralist countries in the world. The various plurality that exist in Indonesia consists of diversity of social class, ethnicity, race, gender, religion, language, and age. This fact leads us to a concept that Indonesia is not formed from one tribe, one culture, one religion, one race and group but precisely Indonesia is formed from diversity. Pluralism very appreciated by the Qur'an society consists of various diverse communities and different. With such diversity and distinction emphasized the necessity of each competing in virtue. The Qur'an is very democratic towards religious pluralism as a phenomenon and does not want a clash between clashes. The Qur’an concept of religious pluralism that has been mentioned in Islamic education is in the form of curriculum, teaching method, delivery of subjects from kindergarten to university to achieve the desired goals. This study attempts to reveal its implementation pluralism in Islamic education, in literary approach.